Critical examination of academic marketing and service research’s philosophical foundation - Tronvoll, Bård; Edvardsson, Bo (The Journal of services marketing, 2024)
Purpose The philosophical foundations determine how an academic discipline identifies, understands and analyzes phenomena. The choice of philosophical perspective is vital for both marketing and service research. This paper aims to propose a social and systemic perspective that addresses current challenges in service and marketing research by revisiting the philosophy of science debate. Design/methodology/approach The paper revisits the philosophy of science debate to address the implications of an emergent, complex and adaptive view of marketing and service research. It draws on critical realism by combining structuration and systemic perspectives. Findings A recursive perspective, drawing on structures and action, is suggested as it includes multiple actors’ intentions and captures underlying drivers of market exchange as a basis for developing marketing and service strategies in practice. This is aligned with other scholars arguing for a more systemic, adaptive and complex view of markets in light of emerging streams in academic marketing and service research, ranging from value cocreation, effectuation, emergence and open source to empirical phenomena such as digitalization, robotization and the growth of international networks. Research limitations/implications The reciprocal dynamic between individuals and the overarching system provides a reflexivity approach intrinsic to the service ecosystem. This creates new avenues for research on marketing and service phenomena. Originality/value This paper discusses critics, conflicts and conceptualization in service research. It suggests a possible approach for service research and marketing scholars capable of responding to current complexities and turbulence in economic and societal contexts.